Raspberry Pi Performance Analysis in Real-Time Applications with the RT-Preempt Patch - Carvalho, Alan; Machado, Cláudio; Moraes, Fabiano (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
This paper presents an analysis of the real-time performance of the Raspberry Pi 3 Model B. Raspberry Pi is a small and low-cost computing device with features that suggest its application as embedded control hardware in mobile robots, aiming the implementation of computer vision and motion control, for example. However, the default operating system of the Raspberry Pi limits its performance in real time. In order to enable it to work in real time, the RT-Preempt patch was installed, which incorporates features of a real-time operating system into Linux. Installing the RT-Preempt patch generates changes to the Linux kernel that reduce its limitations and consequently improve the system's temporal performance. Several system performance tests were performed, measuring the latencies obtained in different situations, such as: polling, timed loop, hardware interrupt and software interrupt. The experimental results confirm a significant improvement in the temporal performance of the system and show the limitations found regarding the use of the Raspberry Pi with the RT-Preempt patch in real-time applications. Based on these results, it can be concluded that it can be used as a low cost solution in non-critical real-time applications.